A Primeron Tax Evasion - Tanzi, Vito (IMF Working Papers; Working Paper ;, 1993)
Tax evasion is universal. It depends on the economic and tax structures, types of income, and social attitudes. The theory of tax evasion has limitations since it depends solely on the attitude toward risk with full information regarding the tax administration's behavior. Methodologies for estimating tax evasion include predominantly estimating the underground economy, and comparing taxes declared with potential tax revenue calculated from national accounts. Actions in addressing tax evasion include use of withholding, presumptive and minimum taxes, selective auditing, penalties, and cross checks between taxes.